The Study of the Semantic Field of Legal Terminology in Persian Language - Mohamed, Nagla Ismail; Salman, Nahla Daoud (Al-Adab Journal, 2021)
In this research٫the Researcher studied the legal words in the legal documents and then studied the statement of the relationship between these words According to the theories. Also ٫the researcher uses the Descriptive analytical method for these terminologies found in the legal Iranian documents. The goal of this study to aim the meaning of a lot of special terminologies that would help the translator during the work.